Pneumatosis cystoides intestinalis: A single center experience - Arikanoglu, Zulfu; Aygen, Erhan; Camci, Cemalettin; Akbulut, Sami; Basbug, Murat; Dogru, Osman; Kirkil, Cuneyt (Baishideng Publishing Group Inc, 2012)
AIM: To share our experience of the management and outcomes of patients with pneumatosis cystoides intestinalis (PCI). METHODS: The charts of seven patients who underwent surgery for PCI between 2001 and 2009 were reviewed retrospectively. Clinical features, diagnoses and surgical interventions of patients with PCI are discussed. RESULTS: Seven patients with PCI (3 males, 4 females; mean age, 50 +/- 16.1 years; range, 29-74 years) were analyzed. In three of the patients, abdominal pain was the only complaint, whereas additional vomiting and/or constipation occurred in four. Leukocytosis was detected in four patients, whereas it was within normal limits in three. Subdiaphragmatic free air was observed radiologically in four patients but not in three. Six of the patients underwent an applied laparotomy, whereas one underwent an applied explorative laparoscopy. PCI localized to the small intestine only was detected in four patients, whereas it was localized to the small intestine and the colon in three. Three patients underwent a partial small intestine resection and four did not after PCI was diagnosed. Five patients were diagnosed with secondary PCI and two with primary PCI when the surgical findings and medical history were assessed together. Gastric atony developed in one case only, as a complication during a postoperative follow-up of 5-14 d. CONCLUSION: Although rare, PCI should be considered in the differential diagnosis of acute abdomen. Diagnostic laparoscopy and preoperative radiological tests, including computed tomography, play an important role in confirming the diagnosis. (C) 2012 Baishideng. All rights reserved.
Keywords: Pneumatosis cystoides intestinalis; Peritoneal free air; Radiological tools; Diagnosis